2022-RA-1087-ESGO Prevalence of exposure to cancer risk factors among apparently healthy childbearing age women. (20th October 2022) - Ng, Chiat Yin; Tan, Pui Yee; Tan, Chung Keat; Bustami, Normina Ahmad; Mitra, Soma Roy; Sing Tan, Eugenie Sin; Chye Ng, Edmond Siah; Wong, Fu Hou; Amini, Farahnaz
Abstract : Introduction/Background: Increased cancer prevalence among women is alarming. Modifiable risk factors account for more than four out of ten cancer-related deaths. This study aimed to investigate the prevalence of exposure to modifiable risk factors along with telomere shortening and DNA damage among women. Methodology: The participants were 134 women without any known medical illness, aged 20–50 years. Validated questionnaires assessed physical activity (PA), working pattern, smoking habit, body mass index (BMI), sleep quality, and psychological distress. Leucocyte telomere length (LTL) and DNA damage were evaluated. Hair heavy metals were quantified using inductively coupled plasma-mass spectrometry. Results: The mean values (±SE) of BMI and LTL were 26.3±0.5kg/m 2 and 5544.9±26.2bp, respectively. Whilst only 4% were smokers, 62% were secondhand smokers. Most participants reported sleep disturbance (95.6%), difficulty in sleep latency (73.1%); 44.8% were poor sleepers. The majority of participants (63.4%) were physically inactive. PA did not meet WHO recommendations and walking contributed the most to the total PA. Psychological distress profile score showed a normal depression and stress levels with a mild level of anxiety. Notably, 56% of the participants were overweight or obese, 35% had abdominal obesity, 48% had at least one metabolic risk factors with 96.3% had vitamin D deficiency (< 50 nmol/L). The amount of fruits and vegetable intake did not meet the Malaysia Dietary Guideline. The prevalence of those who had higher than the normal limit for hair arsenic, cadmium, mercury, lead and chromium were 1.5%, 3.7%, 4.5%, 16.4%, and 66.4% respectively. Also, 50.7% had raised% of tail DNA, and 11.2% had raised tail moment indicating DNA damage. Conclusion: The exposure to cancer risk factors were high among this population, and the potential impact was seen in DNA damage level and telomere shortening, possibly explaining the increasing incidence of cancer.